Efficacy of live attenuated vibrio harveyi vaccine acquired through maternal immunity against Vibrio spp. in zebrafish (Danio rerio F. Hamilton, 1822) - Mohd Hafiz Ngoo, Muhamad Sofie (2022)
Outbreaks of vibriosis in mariculture have caused major setbacks in the aquaculture industry. Vibriosis is a disease that could cause fatal hemorrhagic septicemia and exophthalmia in marine animals. Furthermore, the increase in demand for protein has pushed farmers to utilize a more complex system with higher density to increase output. The demand for fish fry has also pushed the hatchery industry to increase production. However, juvenile fish exposed to vibriosis would develop acute symptoms resulting in high mortality. The vaccination of broodstock could help in tackling the initial immunity delivered to the fish fry to counter this threat. Maternal transfer of immunity helps increase the survivability of fish fry when dealing with harmful pathogens. A live attenuated V. harveyi vaccine (LAVh) from a three-point knock-out on its serine endoprotease gene was established previously. This study aimed to determine the efficacy of three derivatives of the LAVh vaccine on the zebrafish (Danio rerio) model to provide immunological protection against Vibrio alginolyticus, V. parahaemolyticus, and V. harveyi. In the initial study phase, the median lethal dose (LD50) for pathogenic Vibrio spp. in adult zebrafish and 21-days posthatching (dph) zebrafish fry were determined. Subsequently, a vaccine safety study, the antibody level, and the effective dosage of LAVh vaccine to confer 80% survival (ED80) in the adult zebrafish model was determined. As a result, the LD50-144h of V. alginolyticus, V. parahaemolyticus, and V. harveyi in adult zebrafish by intraperitoneal (i.p.) infection was 1 x 105, 106, and 106 CFU/mL respectively. The LD50-144h for the same pathogens in 21-dph juvenile zebrafish by immersion was 1 x 107 CFU/mL. In the second study phase, adult zebrafish were vaccinated by intraperitoneal (i.p.) injection with ED80-144h of LAVh vaccine. The specimens were sampled bi-weekly to plot an antibody profile. Subsequently, on week six (6), the relative percent survival (RPS) of vaccinated adult zebrafish was determined by challenge test. The remaining batches of vaccinated zebrafish were let to spawn and the antibody level of larvae were monitored for 4 weeks post hatching. Results of antibody profiling in the adult zebrafish model indicated that freeze-dried LAVh delivers a longer immunological protective duration. Offspring’s antibody profiling had determined that offspring of the formalin-killed Vibrio harveyi (FKVh) vaccination group had failed to provide immunological protection against V. alginolyticus. The freeze-dried LAVh vaccine was determined as a suitable candidate for further immunological studies. In the final study phase, juvenile zebrafish from freeze-dried LAVh and FKVh were vaccinated by immersion with vaccines formally vaccinated to their predecessor. The vaccination dose was set at 1 x 107 CFU/mL. A sampling of the vaccinated zebrafish juvenile was conducted weekly for four (4) weeks to determine their antibody profile and pro-inflammatory gene expression. At the end of week four (4), the vaccinated juveniles were challenged with pathogenic strains of Vibrio spp. As a result, both groups manages to confer antibody production against antigens Vibrio spp. However, gene expression of pro-inflammatory interleukin 1β (il1β) in the FKVh vaccinated group was elevated for 2 weeks as compared with that of the freeze-dried LAVh vaccinated group. The RPS of both vaccination groups against pathogenic Vibrio spp. displayed 100% immunity. Overall, the freezedried LAVh vaccine manage to confer maternal immune protection for its offspring, provides a long duration of immunological protection, crossprotection coverage against pathogenic Vibrio spp., and a longer shelf-life. It is proposed for the LAVh vaccine to be commercially available for the use of farmers to protect their products against Vibriosis outbreaks.